Asuhan Kebidanan Berkelanjutan Ny. “N” di Rskdia Pertiwi Makassar Tahun 2024 - Endang Sulistyowati (Lembaga Pengembangan Kinerja Dosen, 2024)
Mother and Child Health (MCH) requires efforts through a holistic approach known as Continuity of Care (COC). Continuity is essential throughout a woman's life cycle, including during pregnancy, childbirth, and the postpartum period. To achieve COC, it can be implemented through monitoring and services such as ANC, INC, PNC, and Newborn Care, as well as connecting health care facilities to ensure prompt and accurate handling of emergencies. The aimofthis research is to provide comprehensive midwifery care for pregnant women in the third trimester, during labor, postpartum, care for the newborn, neonates, and family planning. The study was conducted from April to May 2024 at the Special Regional Hospital for Mother and Child, Pertiwi, Makassar. The caremethod in this research involves interviews, observations, and management of the subject 'scare. The subject in this care is Mrs. “N,